Layer‐by‐Layer Electrodeposition of FTO/TiO2/CuxO/CeO2 (1 <x< 2) Photocatalysts with High Peroxidase‐Like Activity by Greatly Enhanced Singlet Oxygen Generation. Issue 7 (18th June 2021) - Shao, Mingzhe; Liu, Dapeng; Yan, Baolin; Feng, Xilan; Zhang, Xiaojuan; Zhang, Yu
Abstract: Inorganic nanomaterials have attracted much attention as enzyme mimics because of simple and stable spatial conformation of those artificially synthesized nanocatalysts. Cu2 O, as an important kind of narrow band gap semiconductor, is identified as effective as visible‐light‐driven photocatalysts, which can catalyze decomposition of H2 O2 into reactive oxygen species. Moreover, after forming Cu x O/CeO2 hybrids, the strongly coupled interface between the two components will further improve their catalytic performance. In this paper, the authors try to construct FTO/TiO2 /Cu x O/CeO2 (1 < x < 2) nanohybrids with such a kind of active interface via a layer‐by‐layer electrodeposition strategy by aid of the following surface etching process. It is found that FTO/TiO2 /Cu x O/CeO2 exhibits good peroxidase mimic activity in the dark but much better performance under visible light irradiation (λ ≥ 420 nm) during catalytic oxidation of 3, 3′, 5, 5′‐tetramethylbenzidine substrates in the presence of H2 O2 . Detailed characterizations disclose that the construction of TiO2 /Cu2 O pn‐heterojunctions do effectively accelerate separation of photogenerated carriers, and the formation of a highly active Cu x O/CeO2 interface is synergistically favorable for selectively generating singlet oxygen to boost the catalytic performance of FTO/TiO2 /Cu x O/CeO2 . Abstract : FTO/TiO2 /Cu x O/CeO2 (1 < x < 2) has a good response to visible light (λ ≥ 420 nm), which can exhibit high peroxidase mimic activity under irradiation. The construction of the TiO2 /Cu2 O pn‐heterojunction and a highly active Cu x O/CeO2 interface is a good solution to accelerate separation of photogenerated carriers and simultaneously increase the synergistic effect between h + and Ce 3+ for enhanced singlet oxygen generation.